Synergistic protection against corrosion of AA2024-T3 by sol-gel coating modified with La and Mo-enriched zeolites - Dias, Susana (2015)
The present work demonstrates an improvement in corrosion protection of sol-gel coatings modified with a mixture of lanthanum and molybdate-enriched zeolite microparticles (La+Mo) due to synergistic effect between lanthanum and molybdate. The effect of these inhibitor species on protection of AA2024-T3 substrate has been studied by Electrochemical Impedance Spectroscopy and Localized Electrochemical Impedance Spectroscopy. Both techniques revealed an enhanced protection when compared with the case where the inhibitors were used alone. The inhibiting mechanism could involve on demand release of molybdate and lanthanum ions from the loaded zeolite followed by the formation of molybdenum oxide/hydroxide and a Mo-Na-La compound on intermetallic particles.